Contributions to Defined Benefit Pension Plans: Economic and Accounting Determinants - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2011)
Pension contribution has a significant impact on firm valuation, employee benefit, and the financial situation of the Pension Benefit Guaranty Corporation (PBGC). Using a comprehensive dataset of defined benefit pension (DB) plan contributions, we investigate economic and accounting determinants of pension contributions. We argue that a firm’s pension contribution decision reflects the trade-off between the benefit – reducing the pension liability, and the cost – reducing cash flows from operations and cash available for other purposes. With respect to economic determinants, we find that firms contribute more when funding status is low and when profitability, cash flows from operations and the marginal tax rate are high, and that firms contribute less when the average retirement benefit and leverage are high. With respect to accounting determinants, we find that firms are less likely to contribute when their default risk is high and when their credit rating is near the investment/non-investment grade cut-off. We also find managers contribute less before insider sales, but only when the funding status is high. Additional analyses indicate that firms behave differently when DB plans are underfunded, during economic downturn periods, and under recent pension accounting regimes.